THE ROLE OF MEDIA IN SHAPING PUBLIC PERCEPTION OF KAZAKHSTAN’S FOREIGN POLICY - Nurpeiis, S.N.; Baubekova, G.K. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
This research paper examines the role of media in shaping public discourse of Kazakhstan image in the global politics. In delves into the question of how media channels – both domestic and international – portray narratives of the state’s foreign policy. This study aims to compare and contrast the representation of articles found in state – controlled and independent Kazakhstani media outlets, as well as Western ones. Key research objectives include the analysis of the framing of Kazakhstan’s foreign policy in both domestic and western media, as well as the exploration of how media representation contributes to either reinforcing or challenging official foreign policy agenda. The given paper use a qualitative content analysis mixed with comparative discourse analysis to examine how Kazakhstan’s foreign policy is presented across different channels of media. This approach allows for comprehensively understanding of the framing strategies used in media narratives, enabling an in-depth study of the ideological and political underpinnings of each media source. The analytical part addresses following key issues: the character of Kazakhstan’s foreign policy, its role in the regional interplay and bilateral, multilateral relations. Besides, more attention will be given to language cues, metaphors, and imagery used to either legitimize or question Kazakhstan’s foreign policy orientation.
Keywords: Kazakhstan; foreign policy; international representation; media outlets; domestic and Western channels; media framing; public dsicourse